Pendidikan Anak Usia Dini dalam Persfektif Alquran - Syamsu Nahar; Zulheddi Zulheddi; Rukiah Rukiah (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
This study aims to determine the elements of early childhood education in the perspective of the Koran. This type of research is library research. In analyzing the data that has been collected the author uses the tahlili method (analysis), which is a method of interpretation used by the commentators in analyzing the content of the verses of the Qur'an. The explanation begins with verses that will explain, explain the description of the contents of the surah, explain the meaning of the lafaz contained in it and then the verses that are clearly described and analyzed so that conclusions can be drawn. The results of the study showed that: 1) Parents as educators for children have roles, including: fostering the religious spirit of children from an early age, developing children's potential and creativity, meeting nutritional needs for children's intelligence. Provide a lawful living for children; 2) The main educational materials that must be taught to early childhood, before other educational materials are given, include: aqidah education and moral education; 3) Learning methods that can be used to carry out education in early childhood, based on QS. Al-Baqarah: 233, Al-An'am: 140, and Ar-Rum: 30, namely: methods of affection, exemplary and habituation methods.